Strategies for Sports Products and Place Management Adopted by Football Club Operators in South-South Nigeria - Chidi Maduanusi, Henry; Christian Elendu, Ifeanyichukwu (British Journal of Marketing Studies, 2020)
This study investigated strategies for sports products and place management adopted by football club operators in south-south, Nigeria. Descriptive survey design was used for the study. The population as well as sample for the study was 450 football club operators. A structured questionnaire titled strategies for sports product and place management questionnaire (SSPPMQ) was used for data collection. The reliability co-efficient of 0.77 was established through test-retest method using Pearson product moment correlation. The generated data were analyzed using mean and standard deviation for research questions, while z-test was used to test the hypotheses at 0.05 alpha level. The findings of the study revealed that, some of the sports products management strategies such as provision of quality sports equipment for sports consumers and sales of quality sports items were not adopted by football club operators in south-south Nigeria. The findings also showed that, some of the sports place management strategies include adequate parking space, clean environment and the lightning inside and around the stadium were not adopted by football club operators in south-south Nigeria. Based on the findings, it was recommended that, sports products should be regulated by sports ministries and the club management should provide adequate parking space, clean environment and the lightning inside and around the stadium.